(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The subject of this research is to study the influence of the technological parameters of knitting on the unravelling of structures, based on the features of the knitted structures, on the analyses made, the technological parameters of the machines as well as on the physical and mechanical properties of the raw materials. Tasks are determined depending on the need to achieve minimum disentanglement of the structures. To achieve complete optimization of the technological process, it is necessary to go through several successive stages: a general study of existing technological methods, development of technologies corresponding to modern norms and requirements, experimental determination of optimal technological parameters to achieve a minimum number of defects in the production of knitted structures, development of technical documentation based on the research done, generation of innovative methods while creating considered structures.